Peningkatan Kompetensi Guru Dalam Melaksanakan Penilaian Sikap Dengan Penilaian Autentik Komprehensif Melalui IHT - Caswita, Caswita; Hidayat, Sukur (Balai Diklat Keagamaan Surabaya, 2023)
This study aims to improve teachers' abilities in assessing aspects of students' attitudes with authentic assessments through in-house training. This research is a school action research (PTS). The research method was carried out through two cycles, carried out at Sindanggalih Elementary School, Tasikmalaya City, for the 2021/2022 academic year. Data obtained through observation and documentation. The results of each cycle were analyzed using a descriptive approach, then used as a reference for further action. Based on the data obtained, it is carried out in three stages, namely the preliminary, core, and closing stages. Trainer skills in implementing in-house training in cycle I is in the high category, namely 60% and has increased to 100% in cycle II. The in-house training model can increase teachers' skills in assessing attitude aspects. This is indicated by the increase in the ability of teachers from being able to the very capable category (50%) in cycle I to being in the very capable category (70%) and capable (30%) in cycle II. In-house training can increase teacher competence in carrying out affective aspect assessments.